Preprosthetic Surgery for Severely Atrophic Maxilla with Poor Palatal Vault Form; Report of Two Cases Treated by Hard Palate Compression through Palatal Vault Osteotomy - IWANARI, Shinkichi; YAMAMOTO, Katsuyuki; HORI, Minoru; MORIYA, Yoshihiko; OKAUE, Masahiro; MATSUMOTO, Mitsuhiko; MATSUNAGA, Shinko; TANAKA, Hiroshi (Journal of Nihon University School of Dentistry, 1993)
Two cases of severely atrophic maxilla with poor palatal vault form treated by Kitayama's modified palatal vault osteotomy technique are described. The advantages of this osteotomy technique are outlined in comparison with other surgical methods.